The Optimal Pricing of Dual-Channel Supply Chain with the Third Party Product Recovery and Sales Effort. (25th June 2020) - Wang, Limin; Song, Qiankun; Zhao, Zhenjiang
Abstract : The optimal pricing of dual-channel supply chain with the third party product recovery and sales effort is considered in this paper. The optimal selling pricing of direct channel and retail channel in the forward supply chain and the optimal collection pricing of retail channel and the third party in the backward supply chain are given for the general case under the centralized and decentralized model. Then, the effect of sales effort of the retailer and the optimal pricing strategy with sales effort under the centralized and decentralized model are provided and analyzed. Finally, the comparative analysis of four situations is carried out by numerical results.